2012
DOI: 10.1002/aur.1259
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Brainstem Function and 4‐Month Arousal‐Modulated Attention Are Jointly Associated With Autism

Abstract: Lay Abstract A stronger preference for high rates of stimulation when tested after feeding at four months of age has been reported in Neonatal Intensive Care Unit (NICU) graduates who later were diagnosed with autism relative to those who were not. This visual preference is typical of newborns, is likely mediated by arousal systems in the brainstem, and should no longer be present by four months. The fact that it was so persistent in babies who later developed autism suggested they may have had atypical brains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 50 publications
(79 reference statements)
2
57
0
1
Order By: Relevance
“…In future, it will be interesting to investigate this question in more detail in order to ascertain whether there is an optimum level between over‐ and understimulation (cf Gardner & Karmel, ; Kidd, Piantadosi, & Aslin, ) and how this differs between individuals. This may relate to previous research that has investigated early individual differences in infants’ preferences for high and low external stimulation from both a state (Gardner & Karmel, ; Geva, Gardner, & Karmel, ) and trait (Cohen et al., ; Gardner, Karmel, Magnano, Norton, & Brown, ; Gardner et al., ; Geva, Schreiber, Segal‐Caspi, & Markys‐Shiffman, ) perspective.…”
Section: Discussionmentioning
confidence: 84%
“…In future, it will be interesting to investigate this question in more detail in order to ascertain whether there is an optimum level between over‐ and understimulation (cf Gardner & Karmel, ; Kidd, Piantadosi, & Aslin, ) and how this differs between individuals. This may relate to previous research that has investigated early individual differences in infants’ preferences for high and low external stimulation from both a state (Gardner & Karmel, ; Geva, Gardner, & Karmel, ) and trait (Cohen et al., ; Gardner, Karmel, Magnano, Norton, & Brown, ; Gardner et al., ; Geva, Schreiber, Segal‐Caspi, & Markys‐Shiffman, ) perspective.…”
Section: Discussionmentioning
confidence: 84%
“…Importantly, a verbal component may be considered. Deviant ABR were reported to predict impaired social interactions, particularly in the context of language disorders and a risk for autism (Cohen et al, 2013). Future study may explore further verbal outcome of neonatal CBSF.…”
mentioning
confidence: 94%
“…at 6-months of age) until their ASD status is relatively certain(16; 20; 21). Because large sample sizes would be required in the general population (at current prevalence estimates(27; 28), over 600 infants would need to be tracked to identify 10 who develop ASD), most prospective studies examine infants at high risk (HR) for developing ASD, such as infant siblings of children with a diagnosis of ASD (though see 2931) as these infants, due to shared genetic liabilities, are at increased risk for ASD themselves. Recent studies of these HR infant siblings have found an over 10-fold increase in autism risk, with 18.7% of HR infant siblings developing ASD(32).…”
Section: Introductionmentioning
confidence: 99%